Pembagian Harta Waris terhadap Anak Angkat Perspektif Maqāşid Syarī’ah - Nabilah Falah Falah; Ahmad Rezy Meidina (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Adopted children cannot return the assets of their adoptive parents and only have rights through a mandatory will, the amount of which cannot be more than 1/3 of the assets left by their adoptive parents as stated in Article 209 paragraph (2) KHI. The fact that happened in the Bobosan sub-district there were 3 (three) cases of inheritance distribution for adopted children who received the entire adoptive parent's inheritance. This paper attempts to explain the distribution of the inheritance of adopted children that occurred in the Bobosan sub-district, Banyumas Regency from the perspective of Maqāşid Syarī'ah. This type of research is field research using an empirical juridical approach. The data source used is from primary data sources in the field by conducting in-depth interviews with the informants studied. The method used in qualitative analysis, namely describing, interpreting and hiding research data. Based on the results of the study, it can be interpreted that the division of inheritance that occurs is the need for Ḍaruriyat adopted children who live dependently living in their parents' house and continue the business of their adoptive parents. So that the family and the surrounding community consider the adopted child to be the full successor of the assets and efforts of the adoptive parents in order to prioritize the benefit of the adopted child. Keywords: Inheritance, Adopted Children